2021
DOI: 10.3390/ani11113199
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Different Levels of Humic Substances Extracted from Worm Compost in Broiler Feeds

Abstract: Different sources and inclusion levels of humic substances (HS) have been tested in broiler rations as an alternative to the addition of growth promoter antibiotics (GPA) with promising results. The current study was carried out to assess the influence of HS extracted from worm compost on broiler production parameters, carcass yield, tibia characteristics, lactic acid bacteria (LAB) counts, excretion of Eimeria oocysts, and antioxidant status of breast meat. A total of 1200 broilers were used, housed in groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(83 reference statements)
3
12
0
Order By: Relevance
“…In several experiments, enhanced final body weight and weight gain and reduced feed conversion ratio have been reported in HS-added broilers using different commercial sources of HS [24,68,113,114]. In agreement with these results, using a liquid or dry extract of HS from worm compost, higher final body weight and weight gain and lower feed conversion ratio have been reported in broiler chickens [19,31,77,146].…”
Section: Productive Response In Animals Supplemented With Humic Subst...mentioning
confidence: 55%
See 2 more Smart Citations
“…In several experiments, enhanced final body weight and weight gain and reduced feed conversion ratio have been reported in HS-added broilers using different commercial sources of HS [24,68,113,114]. In agreement with these results, using a liquid or dry extract of HS from worm compost, higher final body weight and weight gain and lower feed conversion ratio have been reported in broiler chickens [19,31,77,146].…”
Section: Productive Response In Animals Supplemented With Humic Subst...mentioning
confidence: 55%
“…The enhanced immune response in HS-added animals may be the cause of the reduced severity of diarrhea reported in pigs [40][41][42] and calves [43][44][45] and to the strong tendency of lower mortality reported in broilers [25,67,76,77], Japanese quails [27], and pigs [41,78].…”
Section: Immune Response and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended Mn content for broilers is 120 mg/kg during 1–3 weeks and 100 mg/kg during 4–6 weeks by the Feeding Standard of Chicken in China. Additionally, we searched recent related articles on broiler experiments in Animals and also found that the amount of added Mn in the diet was around 100 mg/kg [ 18 , 19 , 20 , 21 , 22 ]. So we added 100 mg/kg Mn in the form of MnSO 4 as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent report, broilers kept in floor pens from 1 to 42 days of age and fed increasing levels of HS from vermicompost, showed lower feed intake (FI) and overall mortality, besides, a better feed conversion rate (FCR) compared to negative control birds not supplemented with HS and positive control birds added with antibiotics (Table 4) [59]. The greatest benefits of adding HS were observed in the last period of the trial, from 29 to 42; these findings closely resemble the observations in previous research.…”
Section: Use Of Humic Substances From Vermicompost In Poultrymentioning
confidence: 99%